Development of fraction domino card media: Validity and practicality for fourth-grade mathematics learning - Kharimah, Asma’ul; Fitrhriyah, Musa’adatul; Hadiyani, Vino Putra (Asatiza: Jurnal Pendidikan, 2025)
The prevalent use of monotonous learning media in elementary mathematics, particularly for difficult topics like fractions, often leads to low student engagement and suboptimal understanding. Game-based learning media, such as domino cards, offer a potential solution by transforming abstract concepts into interactive activities. This study aimed to develop and evaluate the validity and practicality of domino card media for teaching fractions to fourth-grade students. The research followed the Research and Development (R&D) method using the Borg and Gall model. The product underwent a systematic process including expert validation (linguist, media specialist, material expert) and attractiveness testing through individual, small-group, and field trials. The results demonstrated that the domino card media was highly valid, with validation scores of 95% (linguistic), 80% (media), and 85% (material), and highly attractive to students, with trial scores of 96.6% (individual), 94.5% (small group), and 95.7% (field). These findings indicate that the developed media is a valid, practical, and engaging tool for fraction instruction. While this study establishes a strong foundation for its use, the findings warrant further investigation through a quasi-experimental design to empirically verify its impact on student learning outcomes.